Šolska geografija v luči vzgoje in izobraževanja za trajnostni razvoj - Kolnik, Karmen (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
The school curricula were revised in Slovenia on the basis of national guidelines of upbringing and education for sustainable development (VITR), including syllabi for geography. The main aim of the VITR is a strong socio-economic and environmental awareness and the willingness of citizens for personal engagement in the solving of problems. The paper presents the interdependence of the VITR agents in the achievement of goals and the development of students' competences in the case of geography classes, with a special emphasis on the eleven principles of upbringing and education for sustainable development. We analyzed the revised syllabus for geography in grammar schools with a 210-hour programme.
Keywords: curriculum; ecology; ekologija; geografija; geography; kurikulum; Slovenia; Slovenija; sustainable development; trajnostni razvoj; učni programi